Giant boin snake from a Paleocene Neotropical reveal hotter past equatorial temperatures (2009)
The largest extant snakes live in the tropics of South America and southeast Asia1,2,3 where high temperatures facilitate the evolution of large body sizes among air-breathing animals whose body temperatures are dependant on ambient environmental temperatures (poikilothermy)4,5. Very little is known about ancient tropical terrestrial ecosystems, limiting our understanding of the evolution of giant snakes and their relationship to climate in the past. Here we describe a boid snake from the oldest known neotropical rainforest fauna from the Cerrejón Formation (58–60 Myr ago) in northeastern Colombia. We estimate a body length of 13?m and a mass of 1,135?kg, making it the largest known snake6,7,8,9. The maximum size of poikilothermic animals at a given temperature is limited by metabolic rate4, and a snake of this size would require a minimum mean annual temperature of 30–34?°C to survive. This estimate is consistent with hypotheses of hot Palaeocene neotropics with high concentrations of atmospheric CO2 based on climate models10. Comparison of palaeotemperature estimates from the equator to those from South American mid-latitudes indicates a relatively steep temperature gradient during the early Palaeogene greenhouse, similar to that of today. Depositional environments and faunal composition of the Cerrejón Formation indicate an anaconda-like ecology for the giant snake, and an earliest Cenozoic origin of neotropical vertebrate faunas.